Analisis Manajemen Logistik Alat Pelindung Diri di Pt. Waskita Beton Precast. - Heru Winarno; Syaina Ulfah Azhara; Niken Niken (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
Waskita Beton Precast is a company engaged in manufacturing. The products produced include Spun Pile diameter up to 1200mm and other girder products. Every company must have Personal Protective Equipment (PPE). Personal Protective Equipment (PPE) is an effort made to protect or prevent the risk of accidents and also as a complete form of other accident prevention efforts. Therefore, logistics management is needed to meet the needs of personal protective equipment in companies. The purpose of this research is to find out the process of obtaining raw materials and knowing inventory control. The method used is descriptive analysis. The results of this study are that companies obtain personal protective equipment from distributors who have worked with the company. PT. Waskita Beton Precast pre-orders personal protective equipment and completes payment so that personal protective equipment can be sent immediately.